Impact of BCG vaccination on the repertoire of human γδ T cell receptors - Xia, Mei; Blazevic, Azra; Fiore-Gartland, Andrew; Hoft, Daniel F. (Frontiers in Immunology, 2023)
Tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) infection is a serious threat to human health. Vaccination with BCG prevents the development of the most severe forms of TB disease in infants and was recently shown to prevent Mtb infection in previously uninfected adolescents. γδ T cells play a major role in host defense at mucosal sites and are known to respond robustly to mycobacterial infection. However, our understanding of the effects of BCG vaccination on γδ T cell responses is incomplete. In this study we performed γδ T cell receptor (TCR) repertoire sequencing of samples provided pre- and post-BCG vaccination from 10 individuals to identify specific receptors and TCR clones that are induced by BCG. Overall, there was no change in the diversity of γTCR or δTCR clonotypes in post- vs pre-BCG samples. Furthermore, the frequencies of TCR variable and joining region genes were minimally modulated by BCG vaccination at either the γTCR or δTCR loci. However, the γTCR and δTCR repertoires of individuals were highly dynamic; a median of ~1% of γTCR and ~6% of δTCR in the repertoire were found to significantly expand or contract in post- vs pre-BCG comparisons (FDR-q < 0.05). While many of the clonotypes whose frequency changed after BCG were not shared among multiple individuals in the cohort, several shared (i.e., “public”) clonotypes were identified with a consistent increase or decrease in frequency across more than one individual; the degree of sharing of these clonotypes was significantly greater than the minimal sharing that would be expected among cTCR and δTCR repertoires. An in vitro analysis of Mtb antigen-reactive γδT cells identified clonotypes that were similar or identical to the single-chain γTCRs and δTCRs that changed consistently after BCG; pairings of γTCRs and δTCRs that increased after BCG were significantly over-represented among the Mtb-reactive γδT cells (p = 1.2e-6). These findings generate hypotheses about specific γδTCR clonotypes that may expand in response to BCG vaccination and may recognize Mtb antigens. Future studies are required to validate and characterize these clonotypes, with an aim to better understand the role of γδT cells in Mtb immunity.